Net Community Production and Carbon Exchange From Winter to Summer in the Atlantic Water Inflow to the Arctic Ocean - Chierici, Melissa; Vernet, Maria; Fransson, Agneta; Børsheim, Knut Yngve (Frontiers in Marine Science, 2019)
The eastern Fram Strait and area north of Svalbard, are influenced by the inflow of warm Atlantic water, which is high in nutrients and CO2, influencing the carbon flux into the Arctic Ocean. However, these estimates are mainly based on summer data and there are still doubt on the size of the net ocean Arctic CO2 sink. We use data on carbonate chemistry and nutrients from three cruises in 2014 in the CarbonBridge project (January, May, and August) and one in Fram Strait (August). We describe the seasonal variability and the major drivers explaining the inorganic carbon change (CDIC) in the upper 50 m, such as photosynthesis (CBIO), and air-sea CO2 exchange (CEXCH). Remotely sensed data describes the evolution of the bloom and net community production. The focus area encompasses the meltwater-influenced domain (MWD) along the ice edge, the Atlantic water inflow (AWD) and the West Spitsbergen shelf (SD). The CBIO was 2.2 mol C m-2 in the MWD derived from the nitrate consumption between January and May. Between January and August, the CBIO was 3.0 mol C m-2 in the AWD, thus CBIO between May and August was 0.8 mol C m-2. The ocean in our study area mainly acted as a CO2 sink throughout the period. The mean CO2 sink varied between 0.1 and 2.1 mol C m-2 in the AWD in August. By the end of August, the AWD acted as a CO2 source of 0.7 mol C m-2, attributed to vertical mixing of CO2- rich waters and contribution from respiratory CO2 as net community production declined. The oceanic CO2 uptake (CEXCH) from the atmosphere had an impact on CDIC between 5 to 36%, which is of similar magnitude as the impact of the calcium carbonate (CaCO3, CCALC) dissolution of 6% to 18%. CCALC was attributed to be caused by a combination of the sea-ice ikaite dissolution and dissolution of advected CaCO3 shells from the south. Indications of denitrification were observed, associated with sea-ice meltwater and bottom shelf processes. CBIO played a major role (48 to 89%) for the impact on CDIC.